Traditional Science–Practice Research in I-O: Are We Missing the Trees for the Forest?. Issue 4 (December 2017) - Kurtessis, James N.; Waters, Shonna D.; Alonso, Alexander; Jones, Joseph A.; Oppler, Scott H.
Abstract : Abraham Lincoln was fond of saying "killing the dog does not cure the bite" when referring to problems and their persnickety pervasiveness. When thinking about the problems facing the industrial and organizational (I-O) psychology profession, there is no greater source of frustration than the gap between a scientist's findings and the application of those findings to practice. In recent years, organizations such as the White House Behavioral Sciences unit, the Society for Human Resource Management (SHRM) Foundation in partnership with The Economist Intelligence Unit, and many others have explored the gap between research and practice and have highlighted every major derailer, from delays associated with peer-reviewed publication cycles to a lacking infrastructure for bringing science to practitioners. In 2014, the SHRM Foundation even went so far as to implement a strategy based on driving research directly to practitioners through executive round table forums. Despite the best efforts to identify strategies for closing the gap, many organizations have failed to find the optimal means for bringing I-O psychology research to the masses of human resource (HR) practitioners and, in many cases, even I-O psychology practitioners dealing with significant organizational issues.